Analisa Pola Makan dengan Kejadian Hipertensi pada Lansia dan Pralansia di Desa Keureutou Aceh Utara - Muslim Amin; Monalisa Monalisa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Hypertension is defined as an increase in systolic blood pressure of more than 140 mmHg and/or diastolic blood pressure of more than 90 mmHg, measured twice at a five-minute interval while the individual is at rest. One of the major risk factors for hypertension is an unhealthy dietary pattern, including excessive salt intake, high-fat food consumption, and insufficient intake of fruits and vegetables. Hypertension can occur in all population groups, including pre-elderly and elderly individuals. Elderly people experience a decline in physical function, increased susceptibility to diseases, environmental changes, reduced mobility, and various physiological changes that affect their health status. Pre-elderly refers to individuals aged 45–59 years who begin to experience the aging process. This study aimed to determine and analyze the relationship between dietary patterns and the incidence of hypertension among pre-elderly and elderly individuals in Keureutou Village, North Aceh. This research employed a descriptive quantitative method with a correlational analytical approach to examine the relationship between two categorical variables, namely dietary patterns and the incidence of hypertension.